Effects of high-intensity interval training compared to moderate-intensity continuous training on maximal oxygen consumption and blood pressure in healthy men: A randomized controlled trial (2019)
ABSTRACT: Introduction: Aerobic exercise generates increased cardiorespiratory fitness, which results in a protective factor for cardiovascular disease. High-intensity interval training (HIIT) might produce higher increases on cardiorespiratory fitness in comparison with moderate-intensity continuous training (MICT); however, current evidence is not conclusive.Objective: To compare the effects of a low-volume HIIT and a MICT on maximal oxygen consumption (VO2max), systolic blood pressure, and diastolic blood pressure during eight weeks in healthy men between 18 and 44 years of age.Materials and methods: We conducted arandomizedcontrolled trial. Forty-four volunteers were randomized to HIIT (n=22) or MICT (n=22). Both groups performed 24 sessions on a treadmill. The HIIT group completed 15 bouts of 30 seconds (90-95%, maximal heart rate, HRmax), while the MICT group completed 40 minutes of continuous exercise (65-75% HRmax). The study is registered as a clinical trial via clinicaltrials.gov with identifier number: NCT02288403.Results: Intra-group analysis showed an increase in VO2maxof 3.5 ml/kg/min [95% confidence interval (CI) 2.02 to 4.93; p=0.0001] in HIIT and 1.9 ml/kg/min (95% CI -0.98 to 4.82; p=0.18) in MICT. However, the difference between the two groups was not statistically significant (1.01 ml/kg/min. 95% CI -2.16 to 4.18, p=0.52). MICT generated a greater reduction in systolic blood pressure compared to HIIT (median 8 mm Hg; p<0.001). No statistically significant differences were found between the groups for DBP.Conclusions: Results indicated no significant change in VO2maxwith a low-volume HIIT protocol versus MICT after 24 sessions. In contrast, MICT provided a greater reduction in systolic blood pressure compared to HIIT.